Understanding health needs of men who have sex with men in Agra district of India: a community based mixed method study - Aqeel, Khan Iqbal; Chaudhary, S. S.; Misra, S. K.; Royal, Abhishek (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, after decriminalization of homosexuality, men who have sex with men (MSM) emerged as legal community but still one of the most stigmatized section of society. their health needs are distinct due to their distinct behaviour. To achieve ‘Universal health coverage’, this group health needs must be addressed as they had been living in shackles of exclusion. Methods: This mixed method study was conducted in men who have sex with men (MSM) population in Agra district of India. For qualitative part, Audio recorded in-depth interviews were transcribed into verbatim. Potential themes were extracted as a part of analysis as per respondents’ experiences. Data saturation was achieved after 13 IDIs. For quantitative assessment, the snowball technique for sampling was used. First participants were recruited through a non-profit peer group. Further participants were subsequently referred by the participants from their peer circles. Results: Easy /low cost availability of human immunodeficiency virus (HIV) and sexually transmitted disease (STD) testing (32.69%) was foremost cited health need. 26.92% of respondents were unable to tell anything about their health need. 25% of respondents told to increase the number of MSM friendly STD clinics. 15.38% of respondents think that doctor should be taught not to discriminate with MSM and 5.76% asked for psychiatric and medical counselling for MSM. Similarly, qualitative findings highlighted need of non-judgemental and discrimination free health facilities and also suggested MSM inclusive STD centres and psychiatric counselling. Conclusions: The main implication of this study was need to recognize the existence and their diverse health needs and link them to appropriate health care.